Comparison of exercise training and estrogen supplementation on mast cell-mediated doxorubicin-induced cardiotoxicity - Sukanya Phungphong (2020)
Cardiac inflammation has been proposed as one of the primary mechanisms of anthracycline-induced acute cardiotoxicity. A reduction in cardiac inflammation might also reduce cardiotoxicity. This study aimed to evaluate the potential of estrogen therapy and regular exercise on attenuating cardiac inflammation in the context of doxorubicin-induced cardiomyopathy. Ovariectomized rats were randomly allocated into estrogen supplementation, exercise training, and mast cell stabilizer treatment groups. Eight weeks after ovariectomy, rats received six cumulative doses of doxorubicin for two weeks. Echocardiography demonstrated a progressive decrease in ejection fraction in doxorubicin-treated rats without hypertrophic effect. This systolic defect was completely prevented by either estrogen supplementation or mast cell stabilizer treatment but not by regular exercise. As a heart disease indicator, increased β-myosin heavy chain expression induced by doxorubicin could only be prevented by estrogen supplementation. Decrease in shortening and intracellular Ca2+ transients of cardiomyocytes were due to absence of female sex hormones without further effects of doxorubicin. Again, estrogen supplementation and mast cell stabilizer treatment prevented these changes but exercise training did not. Histological analysis indicated that the hyperactivation of cardiac mast cells in ovariectomized rats was augmented by doxorubicin. Estrogen supplementation and mast cell stabilizer treatment completely prevented both increases in mast cell density and degranulation, whereas exercise training partially attenuated the hyperactivation. Our results, therefore, suggest that estrogen supplementation acts similarly to mast cell stabilizers in attenuating the effects of doxorubicin. Ineffectiveness of regular exercise in preventing the acute cardiotoxicity of doxorubicin might be due to a lesser effect on preventing cardiac inflammation.